Shade Tress in Agroforestry Cultivation Systems as a Solution to Improve Environmental Quality and Welfare of Ulubelu Coffee Farmers - Munawaroh, Khoryfatul; Octaviani, Eti Artiningsih; Sari, Nurika Arum; Murda, Rio Ardiansyah; Mulizar, Arif; Prasetya, Kukuh Diki (JURNAL ILMU-ILMU KEHUTANAN, 2023)
This research was based on the condition of the Ulubelu District area, which experienced a decrease in environmental quality and coffee yield productivity. Coffee plantations in Ulubelu District, Tanggamus have experienced a reduction in productivity over the last three years. This reduction in quality is due to the age of the less productive coffee plants (30-40 years) and the lack of shade trees. This study aims to determine the effect of shade trees on coffee productivity and land conditions in coffee agroforestry systems on farmers' land. This research was carried out to increase the productivity of coffee plantations economically and ecologically. The initial stage of this research is collecting secondary data on the application of agroforestry by coffee farmers in the Ulubelu area. The results showed that Ulubelu farmers had implemented agroforestry principles, but they are not optimal in terms of the percentage of shade trees and types of trees planted. Therefore, the recommendation is to plant shade trees of Indigofera sp. with the characteristics of deep roots and the leaves are used to feed cattle. Key words:agroforestry, shading trees, productivity, coffee plants, Ulubelu